2014
DOI: 10.3988/jcn.2014.10.4.314
|View full text |Cite
|
Sign up to set email alerts
|

Dysautonomia in Narcolepsy: Evidence by Questionnaire Assessment

Abstract: Background and PurposeExcessive daytime sleepiness and sudden sleep attacks are the main features of narcolepsy, but rapid-eye-movement sleep behavior disorder (RBD), hyposmia, and depression can also occur. The latter symptoms are nonmotor features in idiopathic Parkinson's disease (IPD). In the present study, IPD-proven diagnostic tools were tested to determine whether they are also applicable in the assessment of narcolepsy.MethodsThis was a case-control study comparing 15 patients with narcolepsy (PN) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…27 Moreover, patients with iRBD often present with impaired autonomic functions and higher SCOPA-AUT scores. 28 In this study, the severity of autonomic disturbances was evaluated by the SCOPA-AUT questionnaire (including the urinary, gastrointestinal, cardiovascular, and thermoregulation systems), and the results showed that patients with higher scores more frequently developed neurodegenerative synucleinopathy diseases. During further analysis of these 4 domains of SCOPA-AUT (sexual disorder being excluded because most information about it could not be collected as a result of Chinese cultures), we found that the converters had higher scores for urinary, gastrointestinal, and cardiovascular systems.…”
mentioning
confidence: 88%
“…27 Moreover, patients with iRBD often present with impaired autonomic functions and higher SCOPA-AUT scores. 28 In this study, the severity of autonomic disturbances was evaluated by the SCOPA-AUT questionnaire (including the urinary, gastrointestinal, cardiovascular, and thermoregulation systems), and the results showed that patients with higher scores more frequently developed neurodegenerative synucleinopathy diseases. During further analysis of these 4 domains of SCOPA-AUT (sexual disorder being excluded because most information about it could not be collected as a result of Chinese cultures), we found that the converters had higher scores for urinary, gastrointestinal, and cardiovascular systems.…”
mentioning
confidence: 88%
“…Neurodegenerative diseases with autonomic disorders can be implicated in hyposmia 37 . There is also an increase in REM sleep behavior disorder and dysautonomy in questionnaire evaluations 38 . Dysautonomy correlates with systemic changes, having an effect not only on the olfactory function but also in body composition and in the increased risk of cardiometabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Narcolepsy is characterized by hypersomnia, cataplexy etc. 7 Although the disease was first described towards the end of the 19th century, the underlying pathomechanisms were described only within the last decade. 8 The exact mechanisms of autoimmunity are poorly understood, but an increase in the incidence of narcolepsy after H1N1 infection and vaccination supported the hypothesis of an immune-mediated pathogenesis of narcolepsy.…”
Section: Discussionmentioning
confidence: 99%